Vocational Life Skills Learning to Improve Entrepreneurship Skills of Deaf Students - Catur Budi Santosa; Siswandari; Bandi; Gunarhadi (Universitas Terbuka, 2025)
: Independence of disabilities is a necessity. This paper is a deskriptive research of vocational life skills learning to improve entrepreneurial skills in SMALB for the deaf. Data collection was conducted through interviews with teachers and distributing questionnaires to students of SMALB Data was collected through observations and interviews with 20 students at SMALB Santi Rama and Pangudi Luhur Jakarta. The results of the observation showed that students preferred Information and Communication Technology (ICT) subjects and had a high interest in working in that field. The obstacle faced was that the abilities possessed by students were not always the same as the design that had been made. The solution to overcome these obstacles is to develop learning methods that are adjusted to the abilities of each student and to hold programs to improve the abilities and skills of teachers. Follow-up in the implementation of the learning program is to involve students in entrepreneurial activities, training or certified internships in the business world and industry (DUDI) and actively participate in various competitions both at home and abroad.